Fecal microbiota transplantation: the power of poop - Liu, Eva; Hou, Maggie (The Meducator, 2018)
Fecal microbiota transplantation (FMT), a procedure involving the transfer of stool from healthy donors to patients, has demonstrated success in re-establishing gut microbiota homeostasis and facilitating the recovery of metabolic and immune function. Based on positive results from numerous clinical trials, current North American and European clinical guidelines recommend FMT as a treatment option for recurrent Clostridium difficile infections. Ongoing investigations into FMT’s efficacy in the treatment of other conditions, such as multiple sclerosis and inflammatory bowel disease, may expand the application of FMT to a myriad of diseases. Nonetheless, challenges regarding biosafety concerns and public perception need to be addressed before FMTs can be considered for broader applications.